A precision-based exercise program for patients with multiple myeloma - Dapunt, Ulrike A.; Ehret, Pauline; Paratte, Jean-Luc; Kühl, Rea; Wiskemann, Joachim; Jäger, Dirk; Müller-Tidow, Carsten; Raab, Marc-Steffen; Goldschmidt, Hartmut (European journal of haematology, 2023)
Objectives Aim of this study was to retrospectively evaluate an interdisciplinary consultation followed by a precision-based exercise program (PEP) for myeloma patients with stable and unstable bone lesions. Methods Data of myeloma patients (n = 100) who received a PEP according to an orthopedic evaluation were analyzed. Bone stability was assessed by established scoring systems (Spinal Instability Neoplastic Score [SINS], Mirels' score). All patients with stable and unstable osteolyses received a PEP and n = 91 were contacted for a follow-up interview. Results In 60% of patients at least one osteolysis of the spine was considered potentially unstable or unstable. Following consultation, the number of patients performing resistance training could be significantly increased (≥2 sessions/week, 55%). Musculoskeletal pain was reported frequently. At the follow-up interview, 75% of patients who performed PEP stated that painful symptoms could be effectively alleviated by exercise. Moreover, only patients who exercised regularly discontinued pain medication. No injuries were reported in association with PEP. Conclusion We were able to demonstrate that individualized resistance training is implementable and safe for myeloma patients. By means of a PEP, patients' self-efficacy in managing musculoskeletal pain was enhanced and pain medication could be reduced.